Study of the influence of thermal factors on the welding process of polyethylene gas pipelines - W. Kiełczynski, S.O. Kishka, M.V. Panchuk, L.S. Shlapak, N. Theremko, M. Szkodo (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2018)
A one-dimensional calculation scheme is proposed with the help of which it is possible to determine and set the technological parameters with the accuracy to be realized in production conditions: the temperature of the heating element and the heating time, which allows maximum mechanization of the technological operations of polyethylene gas pipelines welding. The numerical value of the coefficient of temperature for polyethylene grade PE-80 is determined and it is found that the presence of molten polymer mass at the ends of pipes is an additional source of their heating and a significant factor in obtaining high quality and reliable welds.